Soil Erosion, the Greatest Bottleneck of our National Production - Rao, P. V .C. (Indian Forester, 1949)
The evils of soil erosion are pointed out and illustrated by the happenings in America and the state of affairs in India, generally and the conditions on agricultural lands, in water reservoirs, water ways and harbours, during floods, of water supply, on pasture and forest lands. The losses to roads and bridges are pointed out. The havoc wrought by wind erosion is stated, and the impact on economic and social conditions traced.